Respuesta :
5x + -4y = 13
Solving
-5x + -4y = 13
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '4y' to each side of the equation.
-5x + -4y + 4y = 13 + 4y
Combine like terms: -4y + 4y = 0
-5x + 0 = 13 + 4y
-5x = 13 + 4y
Divide each side by '-5'.
x = -2.6 + -0.8y
Simplifying
x = -2.6 + -0.8y
Simplifying
3x + -4y + -11 = 0
Reorder the terms:
-11 + 3x + -4y = 0
Solving
-11 + 3x + -4y = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '11' to each side of the equation.
-11 + 3x + 11 + -4y = 0 + 11
Reorder the terms:
-11 + 11 + 3x + -4y = 0 + 11
Combine like terms: -11 + 11 = 0
0 + 3x + -4y = 0 + 11
3x + -4y = 0 + 11Combine like terms: 0 + 11 = 11
3x + -4y = 11
Add '4y' to each side of the equation.
3x + -4y + 4y = 11 + 4y
Combine like terms: -4y + 4y = 0
3x + 0 = 11 + 4y
3x = 11 + 4y
Divide each side by '3'.
x = 3.666666667 + 1.333333333y
Simplifying
x = 3.666666667 + 1.333333333y
Solving
-5x + -4y = 13
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '4y' to each side of the equation.
-5x + -4y + 4y = 13 + 4y
Combine like terms: -4y + 4y = 0
-5x + 0 = 13 + 4y
-5x = 13 + 4y
Divide each side by '-5'.
x = -2.6 + -0.8y
Simplifying
x = -2.6 + -0.8y
Simplifying
3x + -4y + -11 = 0
Reorder the terms:
-11 + 3x + -4y = 0
Solving
-11 + 3x + -4y = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '11' to each side of the equation.
-11 + 3x + 11 + -4y = 0 + 11
Reorder the terms:
-11 + 11 + 3x + -4y = 0 + 11
Combine like terms: -11 + 11 = 0
0 + 3x + -4y = 0 + 11
3x + -4y = 0 + 11Combine like terms: 0 + 11 = 11
3x + -4y = 11
Add '4y' to each side of the equation.
3x + -4y + 4y = 11 + 4y
Combine like terms: -4y + 4y = 0
3x + 0 = 11 + 4y
3x = 11 + 4y
Divide each side by '3'.
x = 3.666666667 + 1.333333333y
Simplifying
x = 3.666666667 + 1.333333333y
1) 5x-4y-13=3x-4y-11
2) 5x-4y=3x-4y-11+13 (Add 13 to both sides)
3) 5x-4y+4y=3x-11+13 (Add 4y to both sides)
4) 5x-3x=-11+13 (Subtract 3x from both sides (the -4y and +4y cancel each other))
5) 2x=2 (subtract 5x-3x and add -11+13)
6) x=1 (Divide both sides by 2)
x=1 y=0 or (1,0)
2) 5x-4y=3x-4y-11+13 (Add 13 to both sides)
3) 5x-4y+4y=3x-11+13 (Add 4y to both sides)
4) 5x-3x=-11+13 (Subtract 3x from both sides (the -4y and +4y cancel each other))
5) 2x=2 (subtract 5x-3x and add -11+13)
6) x=1 (Divide both sides by 2)
x=1 y=0 or (1,0)